Portraits of the L2 User - Cook, Vivian (Second Language Acquisition, 2002)
Portraits of the L2 User treats second language users in their own right rather than as failed native speakers. It describes a range of psychological and linguistic approaches to diverse topics about L2 users. It thus provides an innovative overview of current second language acquisition theories, results and methods, seen from a common perspective